Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

Orchard and riparian habitats enhance ground dwelling beetle diversity in Mediterranean agro-forestry systems - da Silva, Pedro Martins; Aguiar, Carlos a S.; de Faria e Silva, Israel; Serrano, Artur R. M.; Faria e Silva, Israel; Serrano, Artur R. M. (Biodiversity and Conservation, 2011)
The relative contribution of mixed orchard and riparian vegetation patches to local and regional diversity of Mediterranean landscapes dominated by cork-oak woodlands was tested in 2006–2007 using ground, rove and darkling beetles (Coleoptera: Carabidae, Staphylinidae, Tenebrionidae). Mixed orchard and riparian gallery habitats recorded higher values of abundance and species richness for overall beetle species, although most darkling beetle species were associated with the sclerophyllous cork-oak woodlands. Ground and rove beetle community structure changed from the orchard and riparian habitats to samples placed 100 m away into the surrounding cork-oak woodland, i.e., non-cork-oak patches enhanced beta diversity within the landscape mosaic. Analysis of ground beetle traits concerning moisture preferences revealed a higher proportion of hygrophilous species in mixed orchard and riparian gallery habitats while xerophilous species were dominant within the cork-oak woodlands. The results of this study suggested that land-use management promoting the maintenance of habitat heterogeneity enhances biodiversity conservation of important hygrophilous and xerophilous species, and subsequently the sustainable use of Mediterranean agro-forest mosaics.
Keywords: 10; 1007; á land-use intensification á; á moisture traits; article; authorized users; Beta diversity; Coleoptera; coleoptera á beta diversity; contains supplementary material; doi; electronic supplementary material the; Land-use intensiﬁcation; Moisture traits; montado; mosaic á sclerophyllous woodland; online version of this; s10531-010-9987-6; Sclerophyllous woodland; which is available to; ‘‘Montado’’ mosaic